2022
DOI: 10.3389/fpubh.2022.825541
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence and DALYs of Urolithiasis From 1990 to 2019: Results From the Global Burden of Disease Study 2019

Abstract: ObjectivesTo provide a comprehensive assessment of the estimated burden and trend of urolithiasis at the global, regional, and national levels.MethodsThe age-standardized rates (ASRs) of the incidence and disability-adjusted life years (DALYs) of urolithiasis from 1990 to 2019 were obtained from the Global Burden of Disease Study 2019 database. Estimated annual percentage changes (EAPCs) were calculated to quantify the temporal trends in urolithiasis burden.ResultsIn 2019, the ASRs of the incidence and DALYs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It was observed that the coexistence of aging and gingivitis or impacted tooth had a synergistic effect on urolithiasis (Figures 2B, C). The ORs (95% CI) for gingivitis in those whose BMI were ≤18.5, 18.5-23.9, 24.0-27.9, and ≥28 kg/m 2 increasing (p for interaction = 0.005) (Supplementary Table 2). We also separately explored the association between oral health conditions and urolithiasis in both genders and observed a closer link between an impacted tooth and urolithiasis in males [OR (95% CI) 1.159 (1.013-1.322) vs. OR (95% CI) 1.361 (1.261-1.468), p for interaction = 0.037] (Supplementary Table 3; Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the coexistence of aging and gingivitis or impacted tooth had a synergistic effect on urolithiasis (Figures 2B, C). The ORs (95% CI) for gingivitis in those whose BMI were ≤18.5, 18.5-23.9, 24.0-27.9, and ≥28 kg/m 2 increasing (p for interaction = 0.005) (Supplementary Table 2). We also separately explored the association between oral health conditions and urolithiasis in both genders and observed a closer link between an impacted tooth and urolithiasis in males [OR (95% CI) 1.159 (1.013-1.322) vs. OR (95% CI) 1.361 (1.261-1.468), p for interaction = 0.037] (Supplementary Table 3; Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Urolithiasis is one of the most common diseases for urologists that affects between 10 and 15% of the world's population ( 1 ). Stone formers suffer from symptoms, high recurrence rate, financial burden, and increased risk of hydronephrosis, renal dysfunction, and renal cell carcinoma ( 2 ). Hence, there is an imperious need to elaborate on the factors affecting the stone formation and accurate prevention strategies against urolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the age-standardized rates (ASRs), the crude rates and the absolute number of MM incidence and mortality were also extracted by sex and age. The ASRs and 95% uncertainty intervals (UIs) were calculated on the basis of GBD 2019 global age-standard population (12).…”
Section: Data Sourcesmentioning
confidence: 99%
“…A present study indicated that currently kidney stones affect about one in 17 adults (the adjusted prevalence rate was 5.8%; 6.5% in men and 5.1% in women) in China ( 3 ). Renal colic caused by urolithiasis is a common complaint in the emergency department and a significant burden for healthcare systems and emergency departments ( 4 ), and it is estimated that this burden is likely to increase over time ( 39 ). Therefore, an improved understanding of the risk factors of urolithiasis is of great significance to public health.…”
Section: Introductionmentioning
confidence: 99%